A Brief Introduction to Parental Involvement in Early Childhood Education in Turkish and Finnish Contexts - Sevcan Hakyemez-Paul (Oslo and Akershus University College of Applied Sciences, 2022)
Research conducted in recent decades has shown the importance of parental involvement in pupils’ well-being, learning, and future academic success as well as their cognitive, social, and emotional development. In addition to these benefits, parental involvement practices improve parental confidence and satisfaction as well as enriching educational programmes, enhancing the climate of educational institutions, and easing teachers’ work burden through responsibility-sharing and increased information flow. Although the significant role of parental involvement is well-supported by various studies, some research reveals that a gap continues to exist between the recommendations of related research and what is practised in educational institutions in reality. This gap explains in part the persistence of insufficient parental involvement practices. This paper, which is based on my public lektio aims to gain a better understanding of early childhood educators’ self-reported reasons for insufficient practices as well as identifying their parental involvement practices and their views in Finnish and Turkish contexts. The study is reported in four original articles, using the quantitative and qualitative data gathered from a representative sample of 287 early childhood educators from Helsinki and 225 early childhood educators from Ankara. Analysis of the results drew attention to the gap between theory and practice as well as the reasons behind this gap from the educators’ point of view. All the data material were discussed for each context, thus allowing for the highlighting of practical implications, which contributed not only to the research on parental involvement practices in different countries but also to the research on identifying factors affecting sufficient parental involvement. In addition to country-centred interpretations, the comparative aspect of this study contributes to existing research into world culture vs. local culture discussions.